2022
DOI: 10.3390/cancers14010249
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Syndromes in Patients with Keratinocyte Skin Cancer

Abstract: A variety of well-characterized cutaneous paraneoplastic syndromes (PNS) are diagnosed during internal malignancies; however, the spectrum of keratinocyte skin neoplasms (KSC) related to PNS is still obscure. The aim of the present review is to compile and evaluate the literature data on PNS associated with a keratinocyte skin neoplasm (KSC). Employing Pubmed, MEDLINE was searched for KSC-associated PNS reports. Forty relevant entries were assembled, reporting a total of 41 PNS cases associated with a KSC (34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In a recent review compiling data on paraneoplastic syndromes (PNS) associated with keratinocyte skin cancers, hypercalcaemia of malignancy was the most common reported PNS and accounted for 78% of the cases, nearly half of the cases had metastatic disease and in 20 out of 21 patients, it was secondary to elevated PTHrP. This reflects the rarity of such association, and possibly the limited capacity of skin cancers to provoke overt PNS 2. Underlying predisposing factors to cSCC reported in those cases included: genodermatoses (dystrophic epidermolysis bullosa,8 porokeratosis of mibelli,9 xeroderma pigmentosum10) and acquired factors, for example, burn scars,11 hidradenitis suppurativa,12 chronic arsenic intoxication13 and lymphoedema 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review compiling data on paraneoplastic syndromes (PNS) associated with keratinocyte skin cancers, hypercalcaemia of malignancy was the most common reported PNS and accounted for 78% of the cases, nearly half of the cases had metastatic disease and in 20 out of 21 patients, it was secondary to elevated PTHrP. This reflects the rarity of such association, and possibly the limited capacity of skin cancers to provoke overt PNS 2. Underlying predisposing factors to cSCC reported in those cases included: genodermatoses (dystrophic epidermolysis bullosa,8 porokeratosis of mibelli,9 xeroderma pigmentosum10) and acquired factors, for example, burn scars,11 hidradenitis suppurativa,12 chronic arsenic intoxication13 and lymphoedema 14…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for 80% of cancer-associated hypercalcaemia 1. HHM has been described with different malignancies, most commonly squamous cell carcinoma (SCC) of the head, neck and lungs, however, for unclear reasons, it is an infrequent association with cutaneous SCC (cSCC) with only a handful of cases reported in the medical literature to date 2. We herein report a case of a patient presenting with a gigantic fungating SCC of the scalp complicated by severe hypercalcaemia due to elevated PTHrP.…”
Section: Introductionmentioning
confidence: 92%
“…Finally, concomitant hypercalcaemia and leukocytosis, forming a paraneoplastic syndrome of hypercalcaemialeukocytosis, was first pointed in tumours of the oral cavity [29] and later confirmed in lung tumours [4]. Its occurrence has also been described in other types of cancer, including carcinoma of the skin [30], bone [31], penis [32], urothelium [33], endometrium [34], tongue [35] and cholangiocarcinoma [36]. Its incidence is lower (0.5% of lung neoplasms at presentation) and associated with worse prognosis than isolated hypercalcaemia but not different from leukocytosis alone [3].…”
Section: Discussionmentioning
confidence: 99%
“…Vlachos, C. et al [ 10 ] compiled data published in the literature on paraneoplastic syndromes (PNS) associated with keratinocyte skin cancer (KSC). They indicate that a prior review publication on this topic was not identified.…”
Section: Clinical Snippetsmentioning
confidence: 99%